Atrial Cardiopathy and Likely Pathogenic Patent Foramen Ovale in Embolic Stroke of Undetermined Source - Leventis, Ioannis A.; Sagris, Dimitrios; Strambo, Davide; Perlepe, Kalliopi; Sirimarco, Gaia; Nannoni, Stefania; Korompoki, Eleni; Manios, Efstathios; Makaritsis, Konstantinos; Vemmos, Konstantinos; Michel, Patrik; Ntaios, George (Thrombosis and Haemostasis, 2020)
Background Atrial cardiopathy and likely pathogenic patent foramen ovale (PFO) are two potential embolic sources in patients with embolic stroke of undetermined source (ESUS). The relationship between these two mechanisms among ESUS patients remains unclear.Methods Atrial cardiopathy was defined as increased left atrial diameter index (> 23 mm/m2) or left atrial volume index (> 34 mL/m2), or PR prolongation (≥ 200 ms), or presence of supraventricular extrasystoles in the electrocardiograms performed during hospitalization for the index stoke. The presence of PFO was assessed by transthoracic echocardiography with microbubble test or by transesophageal echocardiography. The presence of PFO was considered as likely pathogenic if the Risk of Paradoxical Embolism score was 7 to 10.Results Among 367 ESUS patients with available information about the presence of PFO and the presence of atrial cardiopathy (median age: 61 years, 40.6% women), likely pathogenic PFO was diagnosed in 62 (16.9%) and atrial cardiopathy in 122 (33.2%). Only 4 patients (1.1%) had both likely pathogenic PFO and atrial cardiopathy. The prevalence of atrial cardiopathy was lower in patients with likely pathogenic PFO (6.5%) compared with patients with likely incidental PFO (31.2%) or without PFO (40.6%) (Pearson's chi-square test: 26.08, p < 0.001; adjusted odds ratio [OR]: 0.28, 95% confidence interval [CI]: 0.09–0.86). The prevalence of likely pathogenic PFO was lower in patients with atrial cardiopathy compared with patients without atrial cardiopathy (3.3% vs. 23.7%, respectively [Pearson's chi-square test: 24.13, p < 0.001; adjusted OR: 0.2, 95% CI: 0.02–0.6]).Conclusion The presence of atrial cardiopathy is inversely related to the presence of likely pathogenic PFO in patients with ESUS.
Keywords: embolic stroke of undetermined source; patent foramen ovale; RoPE score; atrial cardiopathy